Graphic design : 1 demonstrating the values of good design. (Northfield, IL : Goldsholl Learning Videos, a division of Goldsholl Design & Film Inc., 1989)
This video emphasizes the creative aspect, showing you how to develop new concepts and explore various options and follow actual projects as ideas evolve into finished layouts.
VHS format.
Keywords: Graphic arts -- Techique